Advanced technologies for processing liquid waste of galurgical productions - Mykhaylenko, Volodymyr; Yurchenko, Valentyna; Antonov, Oleksiy; Lukianova, Olha; Gil, Zinaida (Видавництво Львівської політехніки, 2021)
The accumulation of highly mineralized waters and brines in the mining-industrial regions of Ukraine carry a threat of salt pollution of underground and surface water sources. Low-waste processing of these waters is prevented by iron compounds, hydrogen sulfide and sulfur-containing organic compounds. The process of accumulation of iron compounds in brines and groundwater in the presence of hydrogen sulfide has been studied. Comparative calculations of the thermodynamic potentials of the corresponding reactions have been carried out. The calculation results are confirmed by experiments on model solutions and brine of the Dombrovsky quarry. To remove iron compounds from brines and other highly mineralized waters, it is proposed to use electrolysis with inert anodes. It was found that 99.9 % of iron compounds pass into the precipitate of iron hydroxide (III). At the same time, the overwhelming amount of heavy metals also passes into the sediment.
Keywords: brine; iron; groundwater; brine; redox reactions; sulfate reduction; electrolysis; inert anode